Integrasi Nilai-Nilai Islam dalam Psikologi: Upaya Holistik Membangun Kesehatan Mental dan Kecerdasan Emosional - Hanif, Syauqi; Kusumadinata, Husain; Nugroho, Bagas Nurrijal; Firdaus, Hilman; Arief, Armai; Nurdiansyah, Nana Meily (Yayasan Daarul Huda Kruengmane, 2025)
Modern psychology often focuses on the cognitive and emotional aspects of humans, but tends to ignore the spiritual dimension. Islam, as a comprehensive religion, provides a strong spiritual foundation in understanding human behavior and psychological conditions. This paper aims to explore the integration of Islamic values and psychology by highlighting the basic concepts of soul, heart (qalb), reason, and fitrah in Islam. Through principles such as patience, gratitude, and tawakkal, as well as worship practices such as prayer and dhikr, Islam offers a holistic approach to mental health and emotional regulation. In addition, this paper also examines how Islamic values can be applied in psychological education and therapy to shape the character and emotional intelligence of students. This holistic approach is expected to answer the need for a psychological paradigm that is in line with spirituality and divine values.